PIA as an Instrument for Work Environment Management at Arctic Paper Grycksbo - Hjalmarsson, Julia (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
This thesis describes the work of investigating and developing Arctic Paper Grycksbo’s work environment work, focusing on their use of the Paper industry’s information system on work environment (Pappersindustrins Informationssystem om Arbetsmiljö, PIA). The work took place between January and June 2018 as a final part of the Master Programme in Industrial Design Engineering at Luleå University of Technology. The client of the project was Arctic Paper Grycksbo, one of three paper mills in the Arctic Paper Group. The work began with a literature study where areas such as production design, safety, work environment management, risk analysis, etc. was covered. Subsequently, a comprehensive survey of the PIA system was conducted in parallel with a survey of the company’s overall work environment management. This resulted in a clear picture of how the system is used, the role of the system in the work environment management and where there were shortcomings in the work being done today. An identified deficiency was that the quality of investigations of the reported events varied a lot depending on who performed the investigation, another identified deficiency was that there were a number of delayed events that appeared to be investigated and corrected but wasn’t marked as done in the system. To investigate how other companies use the system, a benchmarking was conducted where companies using any variant of the system got to answer how they use the system and what they like about the system. Based on the investigation of the system, Arctic Paper Grycksbo’s use of the system and the use of the benchmarked companies, six areas for improvement was identified, such as the uneven quality of investigation, the delayed events, their use of the risk management module and their analysing of the information in the system. When the areas of improvement were identified, the work was continued to develop how they could improve their use of PIA. First, six of the former benchmarked companies were contacted for more detailed ...